2020
DOI: 10.1097/jcp.0000000000001300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Emotional Adverse Effects of Antidepressants

Abstract: Purpose/Background Emotional adverse effects due to antidepressant use may cause difficulties for the clinician in the treatment of depression. In this prospective study, the emotional adverse effects of antidepressants were evaluated in various aspects. Methods/Procedures Ninety eight patients diagnosed with major depressive disorder were included in the study. At 2nd, 4th, 8th, 12th, and 16th weeks, patients were assessed with Montgomery-Asberg Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, because emotional blunting scores highly correlated with depression severity, it has been concluded that emotional blunting cannot solely be attributed to a medication side effect but should also be considered as a residual symptom of depression ( Goodwin et al, 2017 ). The latter has also been discussed in another study, where emotional blunting scores correlated with MADRS scores and were found to be lower in remitted than in nonremitted patients ( Aşçibaşi et al, 2020 ). Emotional blunting remains an important concern during antidepressant treatment ( Jawad et al, 2023 ).…”
Section: Introductionmentioning
confidence: 60%
“…However, because emotional blunting scores highly correlated with depression severity, it has been concluded that emotional blunting cannot solely be attributed to a medication side effect but should also be considered as a residual symptom of depression ( Goodwin et al, 2017 ). The latter has also been discussed in another study, where emotional blunting scores correlated with MADRS scores and were found to be lower in remitted than in nonremitted patients ( Aşçibaşi et al, 2020 ). Emotional blunting remains an important concern during antidepressant treatment ( Jawad et al, 2023 ).…”
Section: Introductionmentioning
confidence: 60%
“…The authors suggested that emotional blunting is a symptom of depression, which is not measured adequately by conventional scales, such as MADRS (Corruble et al., 2013). Another study revealed that the OQESA score tends to be lower in remitted patients when compared with the non‐remitted group indicating that the scores obtained may not be related to adverse effects of medicines but could be residual symptoms of depression (Aşçibaşi et al., 2020). Moreover, a similar study reported statistically significant correlations between MADRS and OQESA scores at the 8th ( r = 0.346, p = 0.05) and 16th week of antidepressant treatment ( r = 0.490, p < 0.001), respectively (Aşçibaşi et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A further group of studies (n = 5) demonstrated that vortioxetine treatment is associated with affective and cognitive symptoms amelioration in patients with neurological conditions, including neurocognitive decline [115][116][117], Parkinson's disease [118], and post-stroke depression [119]. Interestingly, three studies report data suggesting that vortioxetine could be an effective strategy to reduce SSRI-induced emotional blunting [120][121][122]. Finally, a large number of entries (n = 12) were pharmacovigilance studies or studies whose primary endpoints were safety/tolerability outcomes (main findings summarized in Table 8) [123][124][125][126][127][128][129][130][131][132][133][134].…”
Section: Analytical Observational Studiesmentioning
confidence: 99%